Microbialite response to an anthropogenic salinity gradient in Great Salt Lake, Utah. Issue 1 (14th July 2016) - Lindsay, M. R.; Anderson, C.; Fox, N.; Scofield, G.; Allen, J.; Anderson, E.; Bueter, L.; Poudel, S.; Sutherland, K.; Munson‐McGee, J. H.; Van Nostrand, J. D.; Zhou, J.; et al.
Abstract: A railroad causeway across Great Salt Lake, Utah (GSL), has restricted water flow since its construction in 1959, resulting in a more saline North Arm (NA; 24%–31% salinity) and a less saline South Arm (SA; 11%–14% salinity). Here, we characterized microbial carbonates collected from the SA and the NA to evaluate the effect of increased salinity on community composition and abundance and to determine whether the communities present in the NA are still actively precipitating carbonate or if they are remnant features from prior to causeway construction. SSU rRNA gene abundances associated with the NA microbialite were three orders of magnitude lower than those associated with the SA microbialite, indicating that the latter community is more productive. SSU rRNA gene sequencing and functional gene microarray analyses indicated that SA and NA microbialite communities are distinct. In particular, abundant sequences affiliated with photoautotrophic taxa including cyanobacteria and diatoms that may drive carbonate precipitation and thus still actively form microbialites were identified in the SA microbialite; sequences affiliated with photoautotrophic taxa were in low abundance in the NA microbialite. SA and NA microbialites comprise smooth prismatic aragonite crystals. However, the SA microbialite also contained micritic aragonite, which can be formed as a result of biological activity. Collectively, these observations suggest that NA microbialites are likely to be remnant features from prior to causeway construction and indicate a strong decrease in the ability of NA microbialite communities to actively precipitate carbonate minerals. Moreover, the results suggest a role for cyanobacteria and diatoms in carbonate precipitation and microbialite formation in the SA of GSL.